2018
DOI: 10.7554/elife.31873
|View full text |Cite
|
Sign up to set email alerts
|

Integrative and distinctive coding of visual and conceptual object features in the ventral visual stream

Abstract: A significant body of research in cognitive neuroscience is aimed at understanding how object concepts are represented in the human brain. However, it remains unknown whether and where the visual and abstract conceptual features that define an object concept are integrated. We addressed this issue by comparing the neural pattern similarities among object-evoked fMRI responses with behavior-based models that independently captured the visual and conceptual similarities among these stimuli. Our results revealed … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
157
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 185 publications
(173 citation statements)
references
References 99 publications
(159 reference statements)
12
157
4
Order By: Relevance
“…This is in line with theories on hierarchical message passing in the brain (26)(27)(28). Complex objects are known to be represented in the MTL, such as in perirhinal cortex (31,32), areas known to have direct reciprocal connections with the hippocampus (17,21). Therefore, the hippocampus is ideally positioned to supply complex shape predictions to its immediate cortical neighbours.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This is in line with theories on hierarchical message passing in the brain (26)(27)(28). Complex objects are known to be represented in the MTL, such as in perirhinal cortex (31,32), areas known to have direct reciprocal connections with the hippocampus (17,21). Therefore, the hippocampus is ideally positioned to supply complex shape predictions to its immediate cortical neighbours.…”
Section: Discussionsupporting
confidence: 80%
“…For instance, V2 may supply V1 with predictions about the locations of short line elements making up longer lines (26,29). Visual processing in areas of the medial temporal lobe (MTL) most directly connected to the hippocampus, such as perirhinal and parahippocampal cortices, is dominated by high-level objects and scenes, respectively (30)(31)(32), as well as their spatial, temporal, and associative relations (33)(34)(35).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent model of PRC and PHC function (Burke et al, ), we argued that older adults’ object memory improves when objects are embedded in a rich, semantically related context, due to relatively preserved PHC function during aging (see also, Gutchess, Ieuji, & Federmeier, ). Prior studies have also demonstrated greater PHC activation when an object is semantically bound to a particular context (e.g., a hairdryer in a bathroom; Bar & Aminoff, ; Bar, Aminoff, & Schacter, ; Martin, Douglas, Newsome, Man, & Barense, ). In the current study, all objects were strongly semantically related to the context in which they were observed, and each object and scene pairing was unique.…”
Section: Resultsmentioning
confidence: 96%
“…Another brain structure playing a crucial role in memory of disgust was PRC. Other findings support complex multi-modal item representations in this region 54,55 , such as integration of novel odors with visual category information 56 , or integration of visual with conceptual object features 57 . PRC was also shown to reflect semantic similarity between words 58 , yet here we found no difference in the semantic coherence of word pairs between disgust and fear.…”
Section: Differences In Memory Modulation By Disgust and Fearmentioning
confidence: 81%